2023
DOI: 10.3390/drones7050319
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Air Mobility Operation and Infrastructure for Sustainable Connected eVTOL Vehicle

Abstract: Advanced air mobility (AAM) is an emerging sector in aviation aiming to offer secure, efficient, and eco-friendly transportation utilizing electric vertical takeoff and landing (eVTOL) aircraft. These vehicles are designed for short-haul flights, transporting passengers and cargo between urban centers, suburbs, and remote areas. As the number of flights is expected to rise significantly in congested metropolitan areas, there is a need for a digital ecosystem to support the AAM platform. This ecosystem requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The development of eVTOLs brings operational and safety challenges. To ensure the safe and efficient operation of AAM systems, numerous studies propose frameworks for integrating operations, infrastructure, and air traffic systems in future air transportation and offer feasible solutions [69,70]. Additionally, many researchers focus on the safety of eVTOLs, proposing their own solutions in areas such as regulation and certification, overall vehicle safety, and collision risk mitigation [71][72][73].…”
Section: Factors Affecting User Acceptance In Tourismmentioning
confidence: 99%
“…The development of eVTOLs brings operational and safety challenges. To ensure the safe and efficient operation of AAM systems, numerous studies propose frameworks for integrating operations, infrastructure, and air traffic systems in future air transportation and offer feasible solutions [69,70]. Additionally, many researchers focus on the safety of eVTOLs, proposing their own solutions in areas such as regulation and certification, overall vehicle safety, and collision risk mitigation [71][72][73].…”
Section: Factors Affecting User Acceptance In Tourismmentioning
confidence: 99%
“…The study emphasized that secure and resilient datalinks are necessary to remotely control enroute aircraft. Al-Rubaye et al (2023) found that a lack of adequate wireless coverage in congested cities and disconnected rural communities poses challenges for large-scale AAM deployments [21]. Remote pilots may also need to relay and receive voice commands to maintain compatibility with current air traffic control systems.…”
Section: Traffic Managementmentioning
confidence: 99%
“…Achieving this system necessitates the seamless integration of air traffic management systems, ground control systems, and communication networks to facilitate effective communication between AAM vehicles and ground systems to ensure safe and efficient operations. As a result, the aviation industry is actively working towards developing an innovative aerospace framework that promotes shared aerospace practices, ensuring the safety, sustainability, and efficiency of air traffic operations [14]. A wide range of literature has been published to explore operational strategies and expectations in the context of AAM [15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%